INSTAGRAM ASTROLOGY: A GUIDE OF PREDICTING LIFE DURING THE PANDEMIC TIMES IN INDONESIA - Yuniati, Eka (Jurnal Antropologi Sumatera, 2025)
This article discusses reading horoscopes through social media, which is very popular among young people in Indonesia, and integrates several practical and theoretical perspectives in its analysis. This research explores the zodiac forecast on Instagram in dealing with unbalanced environmental conditions due to the COVID-19. Using qualitative research, data collection involved observation, interviews, and documentation. Observations and interviews were conducted in December 2021 and January 2022 with five people. The results showed that readers’ interest in astrological predictions increased during the pandemic by using Instagram. There are various reasons behind the readers’ interest in seeing and following these predictions, such as encouragement, a way to learn and behave in making choices, as a guide to life, and motivational material for optimistic predictions, especially in facing chaotic and uncertain COVID-19 pandemic conditions. Not only that, astrology in its role is not entirely "believed in" like religion. It is used as a spiritual healing tool and a guide to predict people’s future lives amid unstable environmental conditions due to the pandemic. Using the Instagram platform plays a significant role as a guide for the younger generation, helping them feel more directed in their lives amidst the uncertain conditions of the pandemic.